การพัฒนาแนวทางการดำเนินงานกลุ่มเครือข่ายโรงเรียนขนาดเล็ก สังกัดสำนักงานเขตพื้นที่ การศึกษาประถมศึกษาบึงกาฬ - บัวผัน, จักรพันธ์ (Journal of Graduate School Sakon Nakhon Rajabhat University, 2018)
A study on the development of guidelines and the operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area. The objectives of this study were : 1) elements and indicators to the operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area 2) a study of the present condition and its desirable operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area 3) to develop guidelines to the operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area research is divided into three phases, namely, phase 1 study of elements and indicators to the operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area contributors include experts. The number 5 people using the tools in the research include the assessment phase 2 study the current condition. The condition and how to operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area groups examples include executive education the number of 63 people. The teacher number of 63 people on development operations network group small schools. By the graduate school with best practices (Best Practice) data include executive education and teacher network coordinators from the three schools, including a number of 6 people using the tools in the research include a questionnaire and interviews. Phase 3 development guidelines the operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area include escrow amount 5 people using a process (Focus Group Discussion), a tool used in the research include a discussion group, a statistic that is used in the data analysis is the percent average and standard deviation. The research findings revealed that 1. In this study the elements and indicators the operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area. Overall, appropriate on many levels and is considering a list of aspects found to exist in most of the levels. 1 side is on many levels, 4 side sort average rating descending. Follows their purpose or goal. The side with the participation of the members side members network, leadership of a Coordinator and the things they do together. 2. Results of a study of the current operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area. The moderate. When considering a list of aspects found to exist on many levels. 1 side is moderate with 4 sides. When considering the side list in descending order as follows: mutual activity. Leadership of the Coordinator of network members of network objectives or targets and the participation of the members. The desirable condition the operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area. The overall average very level. When considering a list of aspects found to exist on many levels. 4 sides in level at most 1 side. When considering the side list in descending order as follows mutual activity leadership network coordinator's purpose or goal the side with the participation of the Member and the Member network. 3. To develop guidelines to operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area. Found that the operations network group small schools under jurisdiction office of Bueng Kan Primary Education Service Area contains 5 include. 1) Side with the participation of the members Meeting with teachers, administrators and educators. Developing an information system to monitor treatment. Meeting the parents People in the community and the school board to discuss a common approach. Inviting opportunity for all parties to help the development of the network. Assign responsibility for assessing projects and activities. Together with the community, local government and other agencies in support activities. And participate in the work, emphasizing the teamwork involved. 2) purpose or goal Seminars about the current problems and school needs. Study successful school network. Knowledge-sharing network with a group of schools in the area. Receive comments and suggestions from people both inside and outside. Clearly defined objectives or goals materialistic. 3) leadership of the Coordinator the network Using good governance in the administration. Joint curriculum development Learning process there is research to improve the quality of education. And coordinating with the network of local governments. 4) network members exalted members of the network with outstanding performance. Open to all qualified persons to assist in the development. Support network members can have a role in the operation a thinking process. And the freedom and equality in a unified operation. 5) collaboration activity Joint activities, both academic and sports development activities to continue. Joint development of information system the distribution of power and responsibilities in order to manage effectively. A joint meeting with the school network in at least one time per month. The results of activities to improve the development of the school network.